Positive Impact of Audit Quality on Sharia Banks - Arifin, Muhammad; Riza, Akmal; Ksrisya, Vira Clarissa (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Sharia banking can thrive by using the company's financial success, which is closely aligned with the audit process. The purpose of the audit task is to acquire evidence and assess it impartially to determine if the audit criteria are satisfied, so ensuring a high-quality audit and preventing fraud. Subsequently, a study was conducted to ascertain the influence of ethical factors and auditor expertise on the level of audit excellence in the financial statements of Islamic banks in Banda Aceh. The research employed a quantitative approach, utilizing the multiple linear regression model for data analysis. The primary data was collected through a questionnaire and processed using IBM Statistics to test statistical hypotheses. The study findings indicate that both ethical factors and audit experience have a favorable influence on the quality of audits conducted by Islamic institutions.